Confocal micro-PIV/PTV measurements of the blood flow in micro-channels - Lima, R. (2014)
The development of optical experimental techniques has contributed to obtain explanations on the blood flow behaviour through micro-channels. Although the past results have been valuable, detailed studies on the flow properties of in vitro blood in micro-channels have been limited by several technical factors such as poor spatial resolution and difficulty to obtain quantitative detailed meas-urements at such small scales. In recent years, due to advances in computers, op-tics, and digital image processing techniques, it became possible to combine both particle image velocimetry (PIV) and particle tracking velocimetry (PTV) methods with confocal microscopes. As a result, this combination has greatly increased the resolution of the conventional micro-PIV/PTV systems and consequently pro-vided additional detailed description on the blood cells motion not obtainable by traditional methods. In this chapter the most relevant theoretical and technical is-sues related to both conventional and confocal micro-PIV/PTV methods are dis-cussed. In addition, a comparison between them is presented. Furthermore, the most relevant results of in vitro blood flowing in both glass and polydime-thylsiloxane (PDMS) micro-channels are shown.